2014
DOI: 10.1002/pmic.201400366
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein S100A9, SOD3, and MMP9 as new diagnostic biomarkers for pulmonary tuberculosis by iTRAQ‐coupled two‐dimensional LC‐MS/MS

Abstract: This study aimed to discover the novel noninvasive biomarkers for the diagnosis of pulmonary tuberculosis (TB). We applied iTRAQ 2D LC-MS/MS technique to investigate protein profiles in patients with pulmonary TB and other lung diseases. A total of 34 differentially expressed proteins (24 upregulated proteins and ten downregulated proteins) were identified in the serum of pulmonary TB patients. Significant differences in protein S100-A9 (S100A9), extracellular superoxide dismutase [Cu-Zn] (SOD3), and matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 46 publications
3
74
0
Order By: Relevance
“…We also found that protein S100-A9, extracellular superoxide dismutase [Cu-Zn], and matrix metalloproteinase 9 may represent potential serological markers for TB to distinguish patients with this disorder from healthy controls or those with pneumonia or lung cancer patients [19]. However, the serum protein levels were not ascertained in differential diagnosis groups such as patients with COPD or treated TB cases in either study, and the latter analysis was conducted on only a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that protein S100-A9, extracellular superoxide dismutase [Cu-Zn], and matrix metalloproteinase 9 may represent potential serological markers for TB to distinguish patients with this disorder from healthy controls or those with pneumonia or lung cancer patients [19]. However, the serum protein levels were not ascertained in differential diagnosis groups such as patients with COPD or treated TB cases in either study, and the latter analysis was conducted on only a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial studies include iTRAQ studies of pulmonary tuberculosis (PTB) in humans and mycobacterial infections in cattle . In the works of Xu et al and Wang et al, differences in serum proteome were studied in association with PTB . Included in these was the use of a pooled iTRAQ strategy to compare treated, untreated and cured PTB patients with healthy controls (250 samples in total), in which markers of cured PTB were identified .…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…Markel et al (13) reported that CEACAM1 and MICA could serve as novel serum biomarkers in patients with acute and recurrent pericarditis. Xu et al (14) demonstrated that the candidate serum biomarkers (S100A9, SOD3 and MMP9) performed high sensitivity and specificity in discriminating pulmonary tuberculosis. These findings indicate that serum protein biomarkers serve an important role in the prediction and diagnosis of diseases.…”
Section: Introductionmentioning
confidence: 99%